Antibacterial Activities of Rough Lemon (Citrus jambhiri Lush) Rind Essential Oil - Sembiring, Helmina (Talenta Publisher, 2019)
The isolation of rough lemon (Citrus jambhiri Lush) rind essential oil has been done by using hydrodistillation method and paper disk diffusion test for antibacterial activity test. 2.3 gram (1.51%) of essential oil was obtained from 450 gram of dried rough lemon rind powder. Based on the analysis using GC-MS, the essential oil from rough lemon rind contains 5 chemical compounds, but only 4 of them can be interpreted. They are Limonene (71.88%), 1,4-cyclohexadiene (13.93%), Î²-Pinene (10.57%) and Î²-Ocimene (2.37%). Antibacterial activity was tested to Bacillus cereus and Escherichia coli at 40% concentration (v/v) with 12.7 mm and 12.9 mm of clear zones respectively.